Crosstalk between the CBM complex/NF-κB and MAPK/P27 signaling pathways of regulatory T cells contributes to the tumor microenvironment - Qi, Tongbing; Luo, Ying; Cui, Weitong; Zhou, Yue; Ma, Xuan; Wang, Dongming; Tian, Xuewen; Wang, Qinglu (Frontiers in Cell and Developmental Biology, 2022)
Regulatory T cells (Tregs), which execute their immunosuppressive functions by multiple mechanisms, have been verified to contribute to the tumor microenvironment (TME). Numerous studies have shown that the activation of the CBM complex/NF-κB signaling pathway results in the expression of hypoxia-inducible factor-1 (HIF-1α) and interleukin-6 (IL-6), which initiate the TME formation. HIF-1α and IL-6 promote regulatory T cells (Tregs) proliferation and migration through the MAPK/CDK4/6/Rb and STAT3/SIAH2/P27 signaling pathways, respectively. IL-6 also promotes the production of HIF-1α and enhances the self-regulation of Tregs in the process of tumor microenvironment (TME) formation. In this review, we discuss how the crosstalk between the CARMA1–BCL10–MALT1 signalosome complex (CBM complex)/NF-κB and MAPK/P27 signaling pathways contributes to the formation of the TME, which may provide evidence for potential therapeutic targets in the treatment of solid tumors.